Investigation on a Bangladeshi isolate Bacillus aryabhattai for promising biotechnological applications - Rahman, Mohammad Shahedur; Banu, Rasheda; Moni, Ripa; Islam, Nazmul; Ruma, Mastura Khatun; Zohora, Umme Salma (Jahangirnagar University Journal of Biological Sciences, 2018)
A new isolate was investigated from soil sample collected from Shahrasti upazilla of Chandpur district of Bangladesh. Based on the physico-chemical studies the strain was identified as gram positive Bacilli. Moleculer characterization of the strain was identified as Bacillus aryabhattai which is the first report in Bangladesh. The strain can survive in extreme conditions of salt, temperature and pH. This strain was further characterized and screened for the ability to produce useful enzymes. The optimum temperature for growth and production of these enzymes was within the temperature range 35oC to 40oC. The pH was found to be 7 for its growth and production of different enzymes when investigated over 48 h of incubation. The isolate produced various extracellular enzymes such as α-amylases, cellulases, β-glucosidases, lipases and proteases. The findings of this study provide useful information of the new strain that has potential biotechnological applications. Jahangirnagar University J. Biol. Sci. 7(2): 33-45, 2018 (December)